Reproductive biology of the native forage grass Trichloris crinita (Poaceae, Chloridoideae) - Kozub, Perla Carolina (2017)
Trichloris crinita is a perennial forage grass species native to arid regions of the American continent. Due to its extensive area of distribution, good forage quality and resistance to drought and grazing, this species is widely utilised as forage and for revegetation purposes in environments with low water availability. Despite its importance, genetic improvement of T. crinita has been very limited, partly as consequence of the lack of knowledge on its mode of reproduction. In the present work, we studied the reproductive biology of T. crinita by means of embryological analyses, flow cytometric seed screen (FCSS), self‐compatibility tests and progeny testing with morphological and molecular markers. Cytological analyses revealed embryo sacs with eight nuclei and of Polygonum type for all T. crinita accessions analysed. FCSS histograms exhibited two clear peaks corresponding to 2C and 3C DNA content, indicating embryo sacs of sexual origin. Controlled pollination experiments designed to evaluate seed set (%) demonstrated that T. crinita is self‐compatible, whereas results from morphological and simple sequence repeat (SSR) marker analysis of progeny revealed lack of outcrossing. Together, these results indicate that T. crinita reproduces sexually. It is a self‐compatible and autogamous species. It is expected that these data will have a positive impact in the genetics and breeding of this species, and therefore contribute to its proper utilisation in arid regions.